Acute pain management and perioperative drugs used in low-resource settings. Issue 9 (September 2019) - Phelan, Hannah; Johnson, Tim
Abstract: The choice of drugs used during the perioperative period in low-resourced settings is dictated by numerous factors. The lack of a reliable supply of essential medications coupled with limited provision of trained staff and necessary equipment are the main causative factors. Drugs used may be unfamiliar to anaesthetists from well-resourced settings and those available can vary greatly from day-to-day. For this reason, it is important to develop an understanding of these drugs and their delivery. The management of acute pain benefits from a structured approach such as that used in the RAT model (recognize, assess, treat) from the Essential Pain Management course. This article provides an understanding of the choice of anaesthetic and analgesic drugs used in a low-resourced setting with a focus on those used less commonly in a well-resourced setting.